2012
DOI: 10.1021/bi201862v
|View full text |Cite
|
Sign up to set email alerts
|

Nonionic Homopolymeric Amphipols: Application to Membrane Protein Folding, Cell-Free Synthesis, and Solution Nuclear Magnetic Resonance

Abstract: Nonionic amphipols (NAPols) synthesized by homotelomerization of an amphiphatic monomer are able to keep membrane proteins (MPs) stable and functional in the absence of detergent. Some of their biochemical and biophysical properties and applications have been examined, with particular attention being paid to their complementarity with the classical polyacrylate-based amphipol A8-35. Bacteriorhodopsin (BR) from Halobacterium salinarum and the cytochrome b(6)f complex from Chlamydomonas reinhardtii were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 80 publications
(281 reference statements)
3
93
0
Order By: Relevance
“…This study revealed additional intermolecular contacts with the amphipol (Fig. 9), consistent with the known abilities of amphipols to stabilize MPs compared with detergents [219,220]. Ligand binding [221], conformational dynamics [222] and conformational changes [223,224] of MPs can also be studied using synchrotron radiolysis HRFP.…”
Section: Hydroxyl Radical Footprintingsupporting
confidence: 79%
“…This study revealed additional intermolecular contacts with the amphipol (Fig. 9), consistent with the known abilities of amphipols to stabilize MPs compared with detergents [219,220]. Ligand binding [221], conformational dynamics [222] and conformational changes [223,224] of MPs can also be studied using synchrotron radiolysis HRFP.…”
Section: Hydroxyl Radical Footprintingsupporting
confidence: 79%
“…The Flag-V2R was purified by immunochromatography using an M1 Flag antibody affinity resin (Fig. 1A) and reconstituted by exchanging detergents for NAPols (1:10 protein/ NAPol weight ratio), which are known to enhance the stability of membrane proteins (20). To obtain a homogeneous fraction of the V2R, the NAPol-reconstituted receptors were then loaded onto a size exclusion chromatography column.…”
Section: Resultsmentioning
confidence: 99%
“…The most classical extracts from E. coli and wheat germ are used routinely for structural approaches as they tolerate additives for the cotranslational solubilization of CF system-expressed IMPs. The palette of molecules for protein solubilization in CF systems is now very varied and is increased by the possibility of compounds mixture (Park et al 2011;Bazzacco et al 2012;Junge et al 2010;Ma et al 2011). A valid alternative to tensioactifs is the insertion in lipid bilayer or nanodiscs (Periasamy et al 2012;Roos et al 2012).…”
Section: Production Of Recombinant Impsmentioning
confidence: 99%